Exploring the moderation effect of consumers' demography in the online purchase behavior - Ni Luh Putu Indiani; I Made Suniastha Amerta; Ilham Sentosa (Cogent Business & Management, 2024)
Research findings on the relationship between online purchase intention and actual purchase show inconsistencies, suggesting that intention alone does not adequately predict online purchasing behavior. Field data reveal that only 30% of consumers who express interest in an online product actually make a purchase, challenging the Theory of Planned Behavior (TPB) which asserts that intention significantly influences behavior. This study aims to enhance TPB by examining the moderating effect of consumer demography on the intention-purchase relationship. A survey of 450 internet shoppers was conducted, with data analyzed using Partial Least Square. Results indicate that online purchase intention, eWOM, and trust significantly impact online purchases, with eWOM and trust being fully mediated by online purchase intention. Demographic factors did not moderate the intention-purchase relationship but did influence the trust-purchase relationship. Trust also served as a moderator. Previous studies have explored the moderating effect of demography on factors influencing online purchase intention, but not on the intention-actual purchase relationship, which is the research gap this study addresses.
Keywords: 650; Online purchase intention; trust; eWOM; moderation of consumer demography; online purchase